A Modified Vivaldi Antenna for Improved Angular-Dependent Fidelity Property - Zhi Zeng; Ke Xu; Zhaohui Song; Qinyu Zhang (International Journal of Antennas and Propagation)
The analysis, design, and realization of a modified Vivaldi antenna optimized for time domain fidelity factor in the half-space located in the direction of the antenna main beam are presented. The proposed antenna shows improved angular-dependent fidelity property, with respect to the signal transmitted in the main beam direction. A substantial increase in the fidelity factor is achieved by utilizing spatial filter effect introduced by adding two dielectric slabs parallel to the antenna substrate. By choosing optimal dimensions and location of the slabs, the signal waveforms in the mentioned half-space are equalized so as to improve the quality of the radiated signal waveform in the main beam direction. As a result, the fidelity property in the half-space is improved greatly. The simulated and measured fidelity factor in the angular operational region is studied and compared with experimental measurements. The ranges with the fidelity factor better than the value of 0.9 are improved by 95% in H-plane and by 14% in E-plane, respectively.